Thermodynamic analysis and optimization of the organic Rankine and high-temperature Kalina cycles for recovering the waste heat of a bi-fuel engine. (15th August 2022) - Roeinfard, N.; Moosavi, A.
Graphical abstract: Highlights: Comprehensive test data are extracted for a bi-fuel engine (M15GS engine). A new thermodynamic cycle is used for the engine waste heat recovery. An analysis is applied on the organic Rankine and high-temperature Kalina cycles. Two cycles are optimized by the sensitivity analysis method. The effects of pressure and temperature changes are determined on the system. Abstract: Global warming is currently one of the biggest concerns worldwide; hence, addressing this issue is a trending topic among the research community. Escalating global warming through the wasted energy (30% of its input chemical energy) from internal combustion engines (ICEs) by exhaust emission is a major issue that should be considered. One way to reduce the waste of energy from ICEs is to recover the heat using a thermodynamic cycle. Using this method, not only does the engine power increase but also the fuel consumption decreases. Toward this end, and in this study, the organic Rankine cycle (ORC) and high-temperature Kalina cycle (HTKC), which have been previously used for other purposes, for the first time are utilized for waste heat recovery from the exhaust gases of a Bi-fuel engine. Also, a comprehensive comparison between the performance of the cycles and the limitation of industrialization is considered. The overall goal is to study and optimize these two cycles' overall performance in different operational modes using thermodynamic relationships and sensitivity analysis. In the developed thermodynamic model, the results obtained from the experiment on the Bi-fuel engine are used as the input data. The analysis indicates that the HTKC and ORC can recover 10–25 kW and 2–7 kW power, respectively. Under the investigated operational modes, the efficiency of the HTKC is around 25–40%, and the efficiency of the ORC is between 8 and 13%. Also, the HTKC and ORC cycle can reduce fuel consumption by 20%–30% and 8–10%, respectively. Comparing the performed analysis, it is observed that the performance of the HTKC for waste heat recovery is significantly better than the ORC.